How low can you go? Use of low- and standard-dose liposomal amphotericin B for treatment of invasive fungal infections - Kassamali, Zahra; Danziger, Larry H.; Glowacki, Robert C.; Schwartz, David N. (International journal of infectious diseases, 2013)
Recommended doses of liposomal amphotericin B (L-AMB) range from 3 to 6mg/kg/day, but 1mg/kg/day may be equally effective and a lower cost alternative for many indications. The objective of this analysis was to assess indications and clinical outcomes of patients who received low-dose (1mg/kg/day rounded up in 50-mg increments) and standard-dose (≥2mg/kg/day) L-AMB. This was a retrospective analysis of adult L-AMB recipients with suspected invasive fungal infections (IFI) at a single center from 2006 to 2011. The primary outcome was clinical response at the end of treatment. Secondary outcomes included survival and toxicity. Results were analyzed using Chi-square and descriptive statistics. Of 89 adult L-AMB recipients included, 36 had proven or probable IFIs. Nineteen (53%) received low doses and 17 (47%) received standard doses. Median doses were 1.5 and 3.0mg/kg/day. Cryptococcus was the most common fungal pathogen in the low-dose group (37%), and Candida spp. in the standard-dose group (47%). Forty-seven percent of subjects in both groups improved clinically. Sixty-eight percent of low-dose recipients and 76% of standard-dose recipients survived to discharge. Rates of nephrotoxicity and hypokalemia were comparable. Comparable rates of clinical improvement, survival to discharge, and toxicity were identified among low- and standard-dose L-AMB recipients.